AKTIVITAS DIGITAL PUBLIC RELATIONS DALAM AKUN INSTAGRAM @ORTUSEIGHT - Rona, Ni Made; Sufa, Siska Armawati; Ratnasari, Eny (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
This study aims to determine the activities of Digital Public Relations in the Instagram Ortuseight account and to evaluate. This research uses the concept of Digital Public as an analytical knife. The research method used is qualitative, with data collection techniques interview, observation, and literature study. Digital PR activities are activities of PR practitioners to be able to present messages that can help Ortuseight's branding. So that this account doesn't look too marketable, the caption that accompanies the image is made in a storytelling style. In building social media Instagram Ortuseight accounts, use SEO and Instagram ads. Making professional athletes as sport brand ambassadors by considering the athlete's credibility. Rizky Ridho has carried out his role as Ortuseight's Brand Ambassador well. In the future, it is necessary to evaluate the effectiveness of the Instagram Ortuseight platform.